RIDR-PI-103, ROS-activated prodrug PI3K inhibitor inhibits cell growth and impairs the PI3K/Akt pathway in BRAF and MEK inhibitor-resistant BRAF-mutant melanoma cells. Issue 4 (10th April 2023) - Patel, Hima; Mishra, Rosalin; Wier, Adam; Mokhtarpour, Nazanin; Merino, Edward J.; Garrett, Joan T.
Abstract : Reactive oxygen species (ROS) levels are elevated after acquisition of resistance to v-raf murine sarcoma viral oncogene homolog B1 (BRAF) inhibitors including dabrafenib and MEK inhibitors such as trametinib in BRAF-mutant melanoma. To circumvent toxicity to PI-103 (a pan PI3K inhibitor), we utilized a novel ROS-induced drug release (RIDR)-PI-103, with a self-cyclizing moiety linked to PI-103. Under high ROS conditions, RIDR-PI-103 releases PI-103, which inhibits conversion of phosphatidylinositol 4, 5-bisphosphate (PIP2 ) to phosphatidylinositol 3, 4, 5-triphosphate (PIP3 ). Previous findings demonstrate that trametinib and dabrafenib-resistant (TDR) cells maintain p-Akt levels compared to parental counterparts and have significantly higher ROS. This is a rationale to explore the efficacy RIDR-PI-103 in TDR cells. We tested the effect of RIDR-PI-103 on melanocytes and TDR cells. RIDR-PI-103 exhibited less toxicity compared to PI-103 at 5 µM in melanocytes. RIDR-PI-103 significantly inhibited TDR cell proliferation at 5 and 10 µM. Twenty-four hour treatment with RIDR-PI-103 inhibited p-Akt, p-S6 (Ser240/244) and p-S6 (Ser235/236). We assessed the mechanism of activation of RIDR-PI-103, using glutathione or t-butyl hydrogen peroxide (TBHP) on the TDR cells in the presence or absence of RIDR-PI-103. Addition of the ROS scavenger glutathione to RIDR-PI-103 significantly rescued the cell proliferation in TDR cell lines while addition of the ROS inducer TBHP and RIDR-PI-103 inhibited cell proliferation in WM115 and WM983B TDR cell lines. Examining the efficacy of RIDR-PI-103 on BRAF and MEK inhibitor-resistant cells will expand possible treatment options and open avenues for the development of new ROS-based treatment therapies for BRAF-mutant melanoma patients.